1979
DOI: 10.1073/pnas.76.2.782
|View full text |Cite
|
Sign up to set email alerts
|

Tumor initiators and promoters in the induction of Epstein—Barr virus

Abstract: The effect of various tumor initiators and promoters on induction of persisting Epstein-Barr virus (EBV) in different lines of lymphoblastoid cells was analyzed. Neither five polycyclic aromatic hydrocarbons, amongst them potent tumor initiators (e.g., 7,12-dimethylbenz[a]anthracene), nor the potent (ultimate) liver carcinogen N-acetoxy-N-2-acetylamino-fluorene induced EBV. A series of compounds, representing three classes of tumor-promoting diterpene esters (e.g., 12-O-tetradecanoylphorbol-13-acetate), effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(99 citation statements)
references
References 17 publications
3
96
0
Order By: Relevance
“…Indeed, the effect of HPA-23 on EA expression is quite different in cells induced with antibody to surface immunoglobulin (Tovey et al, 1978), or 12-O-tetradecanoylphorbol 13-acetate (TPA) (Zur Hausen et al, 1979), agents which probably act on the cell surface and do not require internalization. Thus, HPA-23 inhibited EA induction in Raji cells treated concomitantly with anti-/~ immunoglobulin, although pretreatment with the heteropolyanion was without effect (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the effect of HPA-23 on EA expression is quite different in cells induced with antibody to surface immunoglobulin (Tovey et al, 1978), or 12-O-tetradecanoylphorbol 13-acetate (TPA) (Zur Hausen et al, 1979), agents which probably act on the cell surface and do not require internalization. Thus, HPA-23 inhibited EA induction in Raji cells treated concomitantly with anti-/~ immunoglobulin, although pretreatment with the heteropolyanion was without effect (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Zur Hausen et al (1978Hausen et al ( , 1979 demonstrated that phorbol esters which possessed tumour-promoting activity could induce viral cycle in latently infected cells carrying EBV, and Ito et al (1981a) noted that low concentration of n-butyrate increased the effects of tumour promoters synergistically. It is noteworthy that such EBV-activating principles can be considered to possess tumour-promoting capacity (Ito et al, 1981b).…”
mentioning
confidence: 99%
“…Induction of Epstein-Barr virus (EBV) antigens and stimulation of particle synthesis by treatment of the EBV-carrying cell lines with TPA was reported in [ 2,3]. Here we report that TPA exclusively enhances the viral DNA content of cells which harbor papovavirus genomes in a latent episomal state.…”
Section: Introductionmentioning
confidence: 74%
“…To examine whether the tumor-promoting agent has an enhancing effect on such latent HD genomes as in the case of EBV [2,3] we have compared the viral DNA content of a number of HD containing cell lines with and without treatment with TPA. Examples of reassociation kinetic experiments are show in fig.1.…”
Section: Resultsmentioning
confidence: 99%